2020
DOI: 10.3390/nu12082451
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake, Fatigue and Quality of Life in Stable Outpatient Kidney Transplant Recipients

Abstract: Fatigue is a frequent complaint in kidney transplant recipients (KTR), often accompanied by poor quality of life (QoL). The role of nutrition as determinant of fatigue in KTR is largely unexplored. The aims of this study are to examine the association of protein intake with fatigue and QoL in KTR and to identify other determinants of fatigue. This cross-sectional study is part of the TransplantLines Cohort and Biobank Study (NCT03272841). Protein intake was calculated from urinary urea nitrogen (UUN) in 24-h u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Finally, the people we investigated generally did not eat a lot of beans, dairy products, or fish, and their main source of protein was red meat. However, inadequate protein intake, increased nutritional losses, inflammation, oxidative stress, and anabolic or catabolic disorders have been found to lead to high glomerular filtration rates and abnormal kidney function [ 38 40 ]. The association of meat foods and cystatin C may be attributed to changes in circadian rhythms or hormonal effects of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the people we investigated generally did not eat a lot of beans, dairy products, or fish, and their main source of protein was red meat. However, inadequate protein intake, increased nutritional losses, inflammation, oxidative stress, and anabolic or catabolic disorders have been found to lead to high glomerular filtration rates and abnormal kidney function [ 38 40 ]. The association of meat foods and cystatin C may be attributed to changes in circadian rhythms or hormonal effects of diet.…”
Section: Discussionmentioning
confidence: 99%
“… 7 This low number implies that either we are not looking at sarcopenia (or not fully) or maybe the proposed cut‐offs for the diagnosis of sarcopenia are not suitable for the KTR population. Our group recently reported that low muscle mass is a predominant criterion for the diagnosis of malnutrition, 13 and lower protein intake is associated with severe fatigue, lower quality of life, and graft loss and mortality in KTR, 34 , 35 which suggests there is at least a nutritional component at play.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue was assessed using the checklist individual strength 20 revised (CIS20-R), where the subscore of fatigue severity was used (19). Moderate and severe fatigue were defined as scores ≥20 and ≥35, respectively (20,21). To assess HRQoL, a Dutch translation of the Short Form-36 Health Survey was used.…”
Section: Methodsmentioning
confidence: 99%